A DFT Study of the Hydrogen Bonded Structures of Pyruvic Acid–Water Complexes - Hammami, Ferid; Issaoui, Noureddine (Frontiers in Physics, 2022)
The molecular geometries of the possible conformations of pyruvic acid–water complexes (PA-(H2O)n = 1–4) have been fully optimized at DFT/B3LYP/6-311G++ (d, p) levels of calculation. Among several optimized molecular clusters, we present here the most stable molecular arrangements obtained when one, two, three, and four water molecules are hydrogen-bonded to a central pyruvic acid molecule. Appropriate topological and geometrical parameters are considered primary indicators of H-bond strength. Atoms in molecules analysis shows that pyruvic acid can form a ring structure with water, and the molecular structures are stabilized by both strong O–H⋅⋅⋅O and C–H⋅⋅⋅O hydrogen bonds. In large clusters, classical O–H⋅⋅⋅O hydrogen bonds still exist between water molecules, and a cage-like structure is built around some parts of the central molecule of pyruvic acid.